Asch conformity experiment using immersive virtual reality - Kyrlitsias, Christos; Michael-Grigoriou, Despina (My University, 2018)
Virtual reality is used in fields of cognitive sciences to study the participants' behavior. In such cases, existence of other digital humanoid representations in the virtual environment is a crucial factor. Conformity-the act of matching attitudes, beliefs, and behaviors to fit with the majority-is one of the most powerful aspects of social influence. In this study, we investigated conformity to virtual humans in an immersive virtual environment, using two experiments. In the first experiment, we investigated whether agents have social influence on the participants by conducting the 1951 Asch conformity experiment. Findings demonstrate that the participants' response times were affected by the judgments of the agents in the virtual environment. In the second experiment, we used a similar method to study how the factors "agency" and "behavioral real ism" affect social conformity. "Agency" is the extent of a user's belief that other humanoid representations represent real people. "Behavioral realism" is the degree to which humanoid representations behave as they would do in the real world. The results of the experiment showed that conformity can be caused by virtual humans in immersive virtual environments. However, there are no significant results regarding the influence of "agency" and "behavioral realism" on conformity.
Keywords: Agents; Asch experiment; Avatars; Behavioral realism; Conformity; Virtual reality